PERAN DEKRANASDA KOTA PONTIANAK DALAM PENDAMPINGAN PELAKU INDUSTRI KREATIF PADA SEKTOR KRIYA DAN FESYEN - Rama Aisan Putra; Maria Ulfah; Muhammad Basri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstrakThe purpose of this study was to identify and describe the stages and processes of mentoring creative industry players in the craft and fashion fields by the Dekranasda of Pontianak City. This research uses a qualitative approach with the type of case study. Data collection techniques using interviews, observation, and documentation. The results showed that; (1) The preparation of assistance consists of; Recruitment of fostered craftsmen; data collection on the status of craftsmen; data collection on product availability at the UMKM Center in Pontianak City; Identification of problems, needs, and potentials; Develop a work plan or mentoring program; As well as making and submitting activity proposals to the Mayor of Pontianak to get grant assistance. (2) The implementation of assistance consists of; Assistance in improving product quality and competitiveness through production and processing training; Assistance in access to capital from the government and banks; Promotion and marketing assistance through the Pontianak City UMKM Center, Facebook and Instagram, regional, national and international competitions and exhibitions, receiving visits from institutions or agencies and tourists; regular meetings every month; As well as business consulting services. (3) The evaluation of the mentoring program consists of; Evaluation of results and evaluation of processes. The results of the assistance showed that in some craftsmen there was a change and increase in knowledge, creativity and skills, motivation and independence, capital, as well as productivity and business sales. However, in the implementation and achievement of the results, benefits, and objectives of the mentoring program as a whole, it has not been optimal.Keywords: The Role of the Pontianak City Dekranasda, Guidance, Creative Industries in the Craft and Fashion Sector.